Peran orang tua dan guru dalam mengembangkan nilai-nilai karakter anak usia sekolah dasar - Ahmad Yasar Ramdan; Puji Yanti Fauziah (Universitas PGRI Madiun, 2019)
This study aims to (1) analyze the role of parents and teachers in developing children's character; (2) factors that influence children's character development; (3) the impact of the role of parents and teachers on the development of the character of children in SD Muhammadiyah Sapen. This study uses descriptive qualitative research. Data sources were obtained from the principal, class teacher, religious education teacher, committee chairman, and parents. Data collection is done through interviews, observation and documentation. Data was then analyzed by interactive models that followed the format of Miles & Huberman, including: data reduction, data presentation and conclusions. The results showed that the role of parents and teachers as role models for children in attitude and personality, such as honesty, tolerance, discipline, responsibility, religion, and caring for others and the environment. Supporting factors are curriculum content standards, principal leadership, school community commitment, and involve the role of parents in school programs. While the inhibiting factor is the apathy of some parents and teachers, and the lack of parental knowledge about character education. The impact of the role of parents and teachers is: (1) Character values affect children's learning achievement, (2) The occurrence of behavioral changes that occur in children.